Validation of the Spanish version of the Cognitive Emotion Regulation Questionnaire in adolescents - Chamizo-Nieto, María Teresa; Rey-Peña, Lourdes; Sánchez-Álvarez, Nicolás (Colegio Oficial de Psicología del Principado de Asturias, 2020)
Background: The Cognitive Emotion Regulation Questionnaire (CERQ) is an instrument that assesses nine cognitive strategies to cope with negative situations. The aim of this study was to validate the CERQ for a sample of Spanish adolescents, to analyse reliability and validity, and to examine the factor structure by confi rmatory factor analysis. Method: The Spanish version of CERQ (CERQ-S) and other scales (gratitude, emotional intelligence, satisfaction with life, depression, anxiety and stress) were completed by 835 adolescents aged 14-18 (455 girls) from the South of Spain. Results: The results showed that the CERQ-S in adolescents (CERQ-SA) has appropriate psychometric properties with indexes of reliability α = .89 and ω = .96, and the original nine-factor structure was confi rmed. There was also signifi cant correlation between the CERQ-SA and the other scales, showing evidence of convergent validity. Conclusions: The results suggest that the CERQ-SA could be useful for appraising cognitive coping in adolescents. This will help to expand the study and understanding of these strategies, their influence and their consequences for adolescents’ psychological functioning and health.
Validación de la versión española del Cuestionario de Estrategias de Regulación Cognitiva Emocional en adolescentes
Psicothema es una revista de acceso abierto lo que significa que todo el contenido está a disposición de cualquier usuario o institución sin cargo alguno. https://www.psicothema.com/es
Keywords: Psicometría; Adolescentes - Salud mental; Emociones en adolescentes; Cognitive Emotion Regulation Questionnaire; Spanish validation; Cognitive emotion regulation questionnaire; Adolescents; Confirmatory factor analysis